landscape Photography in Mapping Potential Natural Disasters in Ponorogo Regency - Oki Cahyo Nugroho; Deny Wahyu Tricana; Pinaryo Pinaryo (Universitas Muhammadiyah Ponorogo, 2022)
Ponorogo has a natural beauty comparable to that of one of the arts, Reyog Ponorogo. This study is based on the idea of visual communication through landscape photography, which captures the inherent beauty of the area. However, hidden beneath the unique natural beauty comes the risk of catastrophic calamities that endanger life and property. This research creates the natural beauty of Ponorogo, which has the potential for natural catastrophes, by combining geotagging photography techniques and disaster maps from the National Disaster Management Agency (BPBD). Landslides and flash floods are the most major dangers. The government and the people are expected to investigate the combination of nature photography and natural catastrophe maps in order to preserve nature.